HomeMaestro: Order from Chaos in Home Networks - Karagiannis, Thomas; Athanasopoulos, Elias; Gkantsidis, Christos; Key, Peter (2008)
We present HomeMaestro, a distributed system for monitoring and instrumentation of home networks. HomeMaestro performs extensive measurements at the host level to infer application network requirements, and identifies network-related problems through time-series analysis. By sharing and correlating information across hosts in the home network, our system automatically detects and resolves contention over network resources among applications based on predefined policies. Finally, HomeMaestro implements a distributed virtual queue to enforce those policies by prioritizing applications without additional assistance from network equipment such as routers or access points. We outline the challenges in managing home networks, describe the design choices and architecture of our system, and highlight the performance of HomeMaestro components in typical home scenarios.